1989
DOI: 10.1113/jphysiol.1989.sp017654
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and forearm vascular resistance changes after upright bicycle exercise in man.

Abstract: SUMMARY1. Blood pressure, cardiac function and forearm blood flow following voluntary maximal upright bicycle exercise were studied in thirteen normal volunteers in a cross-over design against a control day.2. After exercise there was a short-lived (5-10 min) increase in systolic blood pressure, peak aortic blood velocity and aortic acceleration suggesting a persistence of the positive inotropic influence of exercise.3. Systemic vasodilation, which was seen immediately exercise stopped, lasted at least 60 min.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
1
19

Year Published

1991
1991
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(98 citation statements)
references
References 23 publications
6
69
1
19
Order By: Relevance
“…This may be due to other compensatory mechanisms, such as the baroreflex, that are activated in normotensive subjects, and prevent the degree of PEH from affecting orthostatic tolerance. Although there are reports of gender differences in blood pressure 17 and sympathetic nerve activity, 18 PEH appears to be unaffected by gender, since gender specific 19,20 and mixed gender studies 15,[21][22][23] have found similar degrees of hypotension. It also occurs independent of age, having been observed in young 24,25 middle aged 25 and older adults.…”
Section: Does Peh Occur In All Individuals?mentioning
confidence: 90%
See 4 more Smart Citations
“…This may be due to other compensatory mechanisms, such as the baroreflex, that are activated in normotensive subjects, and prevent the degree of PEH from affecting orthostatic tolerance. Although there are reports of gender differences in blood pressure 17 and sympathetic nerve activity, 18 PEH appears to be unaffected by gender, since gender specific 19,20 and mixed gender studies 15,[21][22][23] have found similar degrees of hypotension. It also occurs independent of age, having been observed in young 24,25 middle aged 25 and older adults.…”
Section: Does Peh Occur In All Individuals?mentioning
confidence: 90%
“…In those studies that have observed a decline in blood pressure following exercise, the average decrement in pressure was approximately 8/9 (SBP/DBP) mm Hg in the normotensive population, 16,[20][21][22][23]25,[31][32][33][34][35] 14/9 mm Hg in the borderline hypertensive population [10][11][12]34,[36][37][38][39] and 10/7 mm Hg in the hypertensive population. 13 37 We recently examined the effects of the exercising muscle mass by comparing the PEH response to both leg and arm ergometry at the same relative intensity.…”
Section: Magnitude Of the Blood Pressure Declinementioning
confidence: 99%
See 3 more Smart Citations